2011
DOI: 10.1179/1433075x11y.0000000046
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport in individual thermoelectric nanowires: a review

Abstract: Extensive research efforts have been devoted to nanowires because of their novel electronic, optical and thermoelectric properties due to spatial confinement in two dimensions. Among various fields, nanowires have been of interest in the thermoelectric community not only for their novel thermoelectric properties but also for their ease of use in fundamental scientific studies as the physics learned using nanowires can be applied in bulk thermoelectric nanocomposites. In this paper, we limit our discussion to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…For example, below a certain critical size (such as the electron mean free path for metallic NPs) NPs can possess some novel properties due to quantum confinement effect. Nanoparticle properties have been studied extensively [163][164][165][166][167][168][169]. The incorporation of nanoparticles into block copolymer matrices can improve existing properties or impart new properties such as mechanical [26,[170][171][172][173][174][175][176][177][178][179][180][181], optical [182], electrical [170,181,[183][184][185][186][187][188], photovoltaic, thermal [149,[189][190][191][192], and barrier [17].…”
Section: Functional Properties Of Block Copolymer -Nanoparticle Compomentioning
confidence: 99%
“…For example, below a certain critical size (such as the electron mean free path for metallic NPs) NPs can possess some novel properties due to quantum confinement effect. Nanoparticle properties have been studied extensively [163][164][165][166][167][168][169]. The incorporation of nanoparticles into block copolymer matrices can improve existing properties or impart new properties such as mechanical [26,[170][171][172][173][174][175][176][177][178][179][180][181], optical [182], electrical [170,181,[183][184][185][186][187][188], photovoltaic, thermal [149,[189][190][191][192], and barrier [17].…”
Section: Functional Properties Of Block Copolymer -Nanoparticle Compomentioning
confidence: 99%
“…It has been experimentally shown that low dimensional thermoelectric materials (superlattices and nanowires) have much enhanced ZT values, 2,3 due to quantum confinement effect and strong phonon boundary scattering. 4 Hence, PbTe nanostructures have recently attracted much attention and been successfully fabricated by many methods, such as solvothermal/hydrothermal synthesis, 5 high temperature solution phase synthesis, 6 chemical bath 7 and thermal evaporation. 8 And various PbTe nanostructures including nanoparticles, 9 nanocubes, 10,11 nanowires or nanorods 12 have been synthesised.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thermoelectric semiconductor materials have some excellent properties, including the lack of noise or moving parts, long lifetime and maintenance-free use. 2 A non-dimensional figure of merit, ZT, which is a direct indication of the thermal efficiency of a power generation device and coefficient of performance for refrigeration devices 3 can be expressed as follows:…”
Section: Introductionmentioning
confidence: 99%